2010
DOI: 10.1186/1471-2431-10-43
|View full text |Cite
|
Sign up to set email alerts
|

Canadian infants' nutrient intakes from complementary foods during the first year of life

Abstract: BackgroundComplementary feeding is currently recommended after six months of age, when the nutrients in breast milk alone are no longer adequate to support growth. Few studies have examined macro- and micro-nutrient intakes from complementary foods (CF) only. Our purpose was to assess the sources and nutritional contribution of CF over the first year of life.MethodsIn July 2003, a cross-sectional survey was conducted on a nationally representative sample of mothers with infants aged three to 12 months. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
40
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 22 publications
5
40
0
4
Order By: Relevance
“…These inappropriate feeding practices have also been observed internationally. A Canadian study from 2010 based on a nationally representative sample of mothers with infants aged 3-12 months found that 83 % of the infants were taking solids at 3 months (14) . Schiess et al studied complementary feeding in five European countries: Germany, Belgium, Italy, Spain and Poland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These inappropriate feeding practices have also been observed internationally. A Canadian study from 2010 based on a nationally representative sample of mothers with infants aged 3-12 months found that 83 % of the infants were taking solids at 3 months (14) . Schiess et al studied complementary feeding in five European countries: Germany, Belgium, Italy, Spain and Poland.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the transition from milk to solid foods is a crucial point to establish life-long feeding patterns (11)(12)(13) . However, poor adherence to recommendations on the introduction of complementary foods has been reported in the Republic of Ireland (ROI) as well as internationally (14)(15)(16)(17)(18) . WHO recommends exclusive breast-feeding during the first 6 months of life of the infant, with the gradual introduction of solids after 6 months (19) .…”
mentioning
confidence: 99%
“…Secondly: iron ID and IDA are not desirable states as the consequences appear to be severe and irreversible if encountered in early infancy [10]. Thirdly: by extending the time of exclusive breastfeeding to 6 months the risk that new food options will not contain sufficient iron is real [2].…”
mentioning
confidence: 99%
“…The first food for infants in North America has traditionally been iron fortified rice cereal [2]. Rice being the least allergenic grain and iron as stores are depleting.…”
mentioning
confidence: 99%
See 1 more Smart Citation